(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
A high level of repurchase will provide big profits for the company to continue to grow. Companies must optimize all resources to continue to increase repurchase intentions for each of their products. It is hoped that this research will be able to determine the role of increasing customer repurchase intentions with service quality, price fairness and store atmosphere at Bendega Restaurant. The entire population is not known with certainty so the sample determined was 140 people. Data was collected by interviews and questionnaires to all respondents. The data was then tested using the multiple linear regression method. The research results show that there is an influence of service quality, price fairness and store atmosphere in significantly increasing repurchase intentions. Suggestions are given to continue to improve service quality, reasonable prices and store atmosphere so that consumers’ repurchase intentions are maximized.